PENINGKATAN LITERASI NUMERASI SISWA KELAS 4 SDN SUKUN 2 MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA MYSTERY BOX SOAL CERITA MATEMATIKA - Afadlil `Ibadirrahman; Andika Gutama; Hidayat, Ahmad Rifki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The results of the 2022 Program for International Student Assessment (PISA)indicate that students` numeracy literacy skills in Indonesia remain low. Thissituation was also observed among fourth-grade students at SDN Sukun 2, whostruggled to solve word problems in mathematics. This study aims to improvestudents’ numeracy literacy skills through the implementation of a Problem-BasedLearning (PBL) model supported by a Mystery Box medium for mathematics wordproblems. The study employed the Classroom Action Research method based onthe Kemmis and McTaggart model, conducted over two cycles with five sessions.The research subjects consisted of 27 fourth grade students at SDN Sukun 2 inMalang City. Data collection techniques included observation, testing, anddocumentation. The results showed that the percentage of students meeting thestandard increased from 40,74% to 96,30%, while the average student score rosefrom 68,44 to 84,51. The implementation of the PBL model supported by the MysteryBox media was effective in improving the numeracy literacy skills of elementaryschool students.